Is Azerbaijan Really Interested In The Implementation Of Renewable Energy? - Mammadli, Sabuhi; Bayramov, Tofig (Acta Carolus Robertus, 2024)
Azerbaijan's energy policy has historically prioritized the development of non-renewable resources, particularly oil and gas, which have been central to the country's economic growth and energy security. The "contract of the century" signed in 1994 catalyzed significant foreign investment, transforming Azerbaijan into a major global energy supplier. This policy focus led to substantial increases in oil and gas production, with proven reserves of approximately 7 billion barrels of oil and 30 trillion cubic feet of natural gas. Despite this, the government has initiated policies to enhance renewable energy contributions, aiming to diversify the energy mix and improve sustainability. Renewable energy's share peaked at 3.1% in 2010 but declined to 1.7% by 2022 due to variability in hydroelectric power. Azerbaijan has considerable potential in wind (3,000 mw) and solar energy (23,040 mw), yet financial constraints, including high-interest rates, have hindered investment. The state budget remains the primary funding source for renewable projects, with us$579.1 million allocated from 2010 to 2022. The government is now actively seeking to attract investment and implement policies to accelerate renewable energy development, aiming to reduce reliance on fossil fuels and promote sustainable energy practices, meanwhile they also continue heavily invest in oil ang gas industry and increase economic cooperation with EU.